"Do something with them!": developing "comfortable" engagement with Elders participating in an arts-based sexual health promotion and STBBI prevention workshop for Indigenous Youth in Labrador, Canada. Issue 1 (1st January 2021) - Landy, Rachel; Worthington, Catherine
ABSTRACT: Although Indigenous Elders were traditionally involved in cross-generational health promotion and education, colonisation disrupted this role. Little research examines the role of Elders in contemporary health promotion for Indigenous youth and few strategies have been identified to engage Elders in health promotion or sexual health education. We explored engagement of Elders through participatory filmmaking in a sexual health and HIV education workshop for youth. Eleven youth and five Elders participated in this 3.5-day workshop. During the workshop, Elders indicated they wanted to make a film and attend a sexual health and HIV education session. Four Elders were interviewed about their experiences. Interview transcripts and the Elders' film were analysed using content analysis. Although Elders initially felt hesitant to engage, the process of participatory filmmaking allowed Elders to co-create an environment for their "comfortable" workshop engagement. Elders' feelings of comfort were created by having control and sense of ownership over their engagement; the presence of youth; peer-based dialogue; inclusion of traditional items; and an Indigenous sexual health educator. Findings suggest participatory filmmaking is a promising approach for engaging and empowering Elders to reclaim traditional roles in sexual health education and health promotion with Indigenous youth.